Flexibly Using the Surveys of Enacted Curriculum to Study Alignment. Issue 2 (6th September 2019) - Polikoff, Morgan S.; Gasparian, Hovanes; Korn, Shira; Gamboa, Martin; Porter, Andrew C.; Smith, Toni; Garet, Michael S.
Abstract: As the standards movement continues into its third decade, there remains a need for alignment methodologies that can be broadly applied to study instruction and policy. This article reports on a series of development efforts meant to revise the Surveys of Enacted Curriculum (SEC) surveys and methods to study the implementation of new college‐ and career‐readiness standards. The work included a meeting of content experts, a series of cognitive interviews, two validation studies, and a small pilot. We discuss both the results of the specific studies and the implications of the work for other potential users of the SEC or SEC‐like tools.